Meghalaya land and revenue mannual - Phira, J.M (Shillong, 1989)
A Comprehensive Manual on Land Administration and related matters in Meghalaya is a long felt need. Administration of land in Meghalaya has distinct features which only Administrators with field experience can comprehend. For convenience and effective administration, a compilation in a volume of the basic Acts, Rules Executive Orders of Meghalaya has been made.
Keywords: Land reforms Maghalaya